PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT TERHADAP HASIL BELAJAR POKOK BAHASAN MENELADANI KETAATAN MALAIKAT- MALAIKAT ALLAH - Arfah, Alfi; Nizar Rangkuti, Ahmad; Annum Dalimunthe, Latifa (IAIN Padangsidimpuan, 2019)
The purpose of this study was to determine whether there was a significant influence on the type of Team Games Tournament cooperative learning model on the learning outcomes of the subject modeled on the obedience of the angels of God Almighty. in class VII of SMP Negeri 5 Padangsidimpuan. This type of research is quantitative research with experimental methods. The population of this research is all grade VII students of SMP Negeri 5 Padangsidimpuan. The research sample is students in Class VII6 and Class VII7. This research instrument is a learning test that meets valid and reliable criteria. The results of this study indicate that there is an influence of the Team Games Tournament cooperative learning model on student learning outcomes. This is indicated from the results of testing the hypothesis by using the t-test obtained tcount t table that is 5.91 2.060 with a significant level of 5%. The results showed that the cooperative learning model Team Games Tournament had a significant effect on student learning outcomes.